ChemInform Abstract: Lithium‐Filled Double‐Deck Layered Structure of the RELixCu2‐yP2 (RE: La, Pr, Nd, Gd, Er; 0.82 ≤ x ≤ 1; 1.19 ≤ y ≤ 1.54) Series: Experimental and Theoretical Studies. Issue 35 (September 2015) - Jang, Eunyoung; Nam, Gnu; Woo, Hyein; Lee, Junseong; Han, Mi‐Kyung; Kim, Sung‐Jin; You, Tae‐Soo
Abstract LaLi0.92Cu1.33P2, PrLi0.98Cu1.54P2, NdLi0.91Cu1.42P2, GdLiCu1.48P2, and ErLi0.82Cu1.19P2 are synthesized from the elements (Nb ampule, 1100 °C, 10 h).